Clinical management of early-stage cervical cancer: The role of sentinel lymph node biopsy in tumors ≤2 cm. (October 2019) - Diaz-Feijoo, Berta; Temprana-Salvador, Jordi; Franco-Camps, Silvia; Manrique, Susana; Colás, Eva; Pérez-Benavente, Asunción; Gil-Moreno, Antonio
Abstract: Objective: To evaluate the experience with sentinel lymph node (SLN) biopsy in patients with early-stage cervical cancer at our hospital, and to analyze factors influencing the rate of false negatives. Study design: This study was carried out at the Vall d'Hebron Hospital (Barcelona, Spain) between September 2000 and October 2016. All patients underwent SLN biopsy and systematic and bilateral pelvic lymphadenectomy, followed by radical hysterectomy. SLNs were analyzed by the pathologist by staining with hematoxylin-eosin and immunohistochemistry. Results: Patients (N = 128) had been diagnosed with early-stage cervical cancer (FIGO-2009 stages 1A2, IB1, and IIA1). The combined SLN detection rate (99-technecium and a blue dye) was 98.4%, bilateral in 76% of the patients. Positive SLNs were found in 19 patients (14.8%). Sensitivity of detection was 79.2% (CI95, 57.9–92.9), false negative rate 20.8% (CI95, 7.1–42.2), and negative predictive value 95.4% (CI95, 89.6–98.5). False negative cases were observed in 5 patients with tumors >2 cm and presenting lymphovascular space invasion. Micrometastases were detected during SLN ultrastaging in 3 patients (2.3%). The median follow-up was 8.24 years and the 5-year overall survival (OS) was 88.4% (CI95, 80.9–93.1). Conclusion: SLN mapping and biopsy in early-stage cervical cancer is feasible and has high sensitivity to detect patients with initial metastases. The risk of false negatives could be lower in certain groups of patients, such as those with tumors ≤2 cm and no lymphovascular space invasion, but future studies will be required to test this hypothesis.